EKSTRAKSI MINYAK NABATI DARI SCENEDESMUS SP. MENGGUNAKAN GELOMBANG MIKRO - Linda Septiyaningsih; Satwiko Sidopekso; Noor Fachrizal (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2012)
Microalgae is one of the raw material for biodiesel. Types of microalgae that used in this research is Scenedessmus Sp. because it has a high content of vegetable oils. Solution of microalgae used do not need to be dried first. It aims to keep the microalgae cells from damage and keeping the lipid content contained in its. Extraction of vegetable oil and microalgae Scenedessmus Sp. used Microwave Assisted Process method. The sample solution Scenedessmus Sp. used 200 mL for the extraction of vegetable oils from microalgae is 380 Watt and the variation time are 2, 3, and 4 minutes. The results showed microalgae cells burst after the extraction so that it can be concluded that the microwaves are used to extract vegetable oil from microalgae. Keywords: minyak nabati, microalgae, Scenedesmus sp., microwave assisted process.